Copper stress in grapevine: Consequences, responses, and a novel mitigation strategy using 5-aminolevulinic acid. (15th August 2022) - Yang, Yuxian; Fang, Xiang; Chen, Mengxia; Wang, Lingyu; Xia, Jiaxin; Wang, Zicheng; Fang, Jinggui; Tran, Lam-Son Phan; Shangguan, Lingfei
Abstract: Improper application of copper-based fungicides has made copper stress critical in viticulture, necessitating the need to identify substances that can mitigate it. In this study, leaves of 'Shine Muscat' ('SM') grapevine seedlings were treated with CuSO4 solution (10 mM/L), CuSO4 + 5-aminolevulinic acid (ALA) (50 mg/L), and distilled water to explore the mitigation effect of ALA. Physiological assays demonstrated that ALA effectively reduced malondialdehyde accumulation and increased peroxidase and superoxide dismutase activities in grapevine leaves under copper stress. Copper ion absorption, transport pathways, chlorophyll metabolism pathways, photosynthetic system, and antioxidant pathways play key roles in ALA alleviated-copper stress. Moreover, expression changes in genes, such as CHLH, ALAD, RCA, and DHAR, play vital roles in these processes. Furthermore, abscisic acid reduction caused by NCED down-regulation and decreased naringenin, leucopelargonidin, and betaine contents confirmed the alleviating effect of ALA. Taken together, these results reveal how grapevine responds to copper stress and the alleviating effects of ALA, thus providing a novel means of alleviating copper stress in viticulture. Graphical abstract: Image 1 Highlights: Exogenous application of 5-aminolevulinic acid alleviates copper stress in grapevine. ALA restores suppressed photosynthesis under copper stress. Antioxidant systems and phytohormone metabolism were induced to alleviate copper stress.